Organizace volejbalového turnaje - Lanč, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Cílem bakalářské práce je na základě analýzy volejbalového turnaje smíšených družstev navrhnout vhodná řešení pro optimální řízení turnaje a dále zlepšení jeho finančního zabezpečení a navrhnutí doporučení, které povedou ke zvýšení zisku. Práce je rozdělena do tří částí. První část se za pomocí literárních zdrojů zabývá organizací sportovních akcí a finančním zajištěním akce. V druhé části je zahrnuta analýza volejbalového turnaje smíšených družstev. Poslední kapitola obsahuje návrh změn v řízení turnaje a efektivnější využití finančních zdrojů.

The purpose of this thesis is to propose suitable solutions for the tournament management based on analysis of mixed team volleyball tournament, to improve its financial security and to suggest recommendations leading to further increases of profits. The thesis is separated into three sections. First addresses the organization of sporting events, with the help of literary sources, and the funding of events. The second section includes the analysis of the mixed team volleyball tournament. The last section contains the recommendations for changes in the management of the tournament and for it’s more effective use of financial resources.
Organisatoin of Volleyball Tournament
Keywords: Volejbal; turnaj; organizování; smíšená družstva; sportovní management; SWOT analýza.; Volleyball; tournament; organisation; volleybal mixed team sports management; SWOT analysis.